Etanercept protects remote organ damage in a rat model of thermal injury [Etanersept sıçan yanık modelinde uzak doku hasarında koruyucudur] - ŞENER, GÖKSEL; ÇETİNEL, ŞULE; TETİK, ŞERMİN; ŞENER, TARIK EMRE (Marmara University, 2011)
Thermal injury may lead to systemic inflammatory response, and multiple organ failure. This study was designed to determine the possible protective effect of etanercept treatment against oxidative damage in the lung tissue induced by burn injury. Under ether anaesthesia, the shaved dorsum of rats was exposed to a 90°C bath for 10 s to induce burn injury. Etanercept (1 mg/kg) or saline was administered intraperitoneally immediately after and at 24th hour burn injury. Rats were decapitated at 6 h and 48 h following burn injury and trunk blood was collected to assay pro-inflammatory cytokines (TNF-α and IL-1β), lactate dehydrogenase (LDH) activity. In order to evaluate the presence of oxidant injury lung tissue samples were taken for the determination of malondialdehyde (MDA) and glutathione levels, myelopreoxidase (MPO) and Na+-K+ ATPase activities. Tissues were also examined microscopically. Severe skin scald injury (30% of total body surface area) caused a significant decrease in GSH level and Na+-K+ ATPase activity, which was accompanied with significant increases in MDA level, MPO activity. Similarly, serum TNF-α, IL-1β and LDH were elevated in the burn group as compared to control group. On the other hand, etanercept treatment reversed all these biochemical indices, as well as histopathological alterations, which were induced by thermal trauma. Findings of the present study suggest that etanercept possesses an anti-inflammatory effect on burn-induced pulmonary damage and may be beneficial in thermal trauma.
Keywords: Burn; Cytokine; Etanercept; Lipid peroxidation; Myeloperoxidase